A study of printing plate mould development by using 3d printers for micro-flexographic printing process - Hassan, S.; Yusof, M.S.; Embong, Z.; Ding, S.; Marwah, O.M.F. (Universiti Teknikal Malaysia Melaka (UTEM), 2020)
Micro-flexographic is a new printing technique that has been implemented by combining flexographic printing and micro-contact printing technique. Flexographic printing is generally a high-speed production in roll to roll printing technique widely used in the graphic printing industry. Micro-contact printing technique is usually employed to produce fine solid line structures in micro to nano scale. Mould preparation for printing plate is also one of the vital parameters in micro to nano scale image printing. A precise mould could be used to produce the most accurate printing plate for micro-flexographic printing. The three dimension (3D) printer has the capability of producing fine solid lines below 100 μm in width and gap on master mould for the printing industry. This research elaborated the use of various 3D printers to produce a master mould for micro-flexographic printing. This paper investigated the capability of multiple 3D printers in creating micro to nano fine solid lines in the master mould for future development and application of printing in the electronic, graphic and bio-medical field.